The existence of cyberbullying results in psychological consequences among students: A review - Noorhafeza Herliani Adey; Sharon Kwan Sam Mee; Carmella E. Ading (Southeast Asia Psychology Journal, 2024)
The abstract critically examines the research methodology used in the current literature on cyberbullying, with a specific focus on the period from 2019 to 2023. It includes full-text articles, mixed-methods research designs, and English language studies involving student samples. The primary aim is to summarize psychological findings, identify strengths and limitations in selected studies, and contribute to the advancement of research in this area. The review systematically analyzes methods used in the selected studies and their implications for understanding the psychological impact of cyberbullying. It also discusses the results and findings, explaining how different cyberbullying approaches affect students' mental health. Additionally, the review provides recommendations for future research and emphasizes the need for a multidisciplinary approach to address the complex nature of cyberbullying and its impact on students